Intratympanic steroids versus oral steroids in idiopathic sudden sensorineural hearing loss, hospital-based study - Alil, Arshed; Shafi, Omar Mohammad; Deeba, Farah (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Introduction: Idiopathic sudden sensorineural hearing loss (ISSHL) is defined as a hearing loss of 30 dB or more, affecting at least 3 consecutive frequencies, occurring within 3 days without any identifiable cause. To find the effectiveness of intratympanic steroid injection (ITS) for hearing recovery and comparing the results with oral steroids therapy. Materials and Methods: This prospective study was done in the department of ENT, Govt medical college, Srinagar, over a period of two years. A total 60 patients of ISSHL was selected for the study. Through examination, otoscopy and pure tone audiometry (PTA) was done for all the cases before initiation of therapy. Thirty patients received and thirty patients received oral prednisolone for a protocol-based dose and duration. PTA was repeated every two weeks over duration of two months for documentation of improvement of hearing on pure tone four frequency averages. Results: Chances of recovery were more with middle ear injection group in 18 patients (60%) in comparison to oral steroids in 14 patients (46.66%). Complete recovery was found in six cases (20%) in injection group and four cases (13.33%) in oral steroid group. The ITS group showed a better control of associated symptoms like dizziness, tinnitus and vertigo are controlled better with ITS (73.33%) than oral steroid group (56.66%). The ITS group showed faster recovery also with lower side effects. Conclusion: Intratympanic dexamethasone injection is more effective in comparison to oral prednisolone for the management of ISSHL, however larger studies may be required.